ANALISIS POLA HIDUP PADA PASIEN HIPERTENSI DI PUSKESMAS BALANGNIPA KECEMATAN SINJAI UTARA KABUPATEN SINJAI - herlina herlina (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Base on data wich is obtain from public health center balingnipa sinjai regency on 2015 hypertension incidence rate 1.001 person, in 2016, 900 person and 2017 has increased to 1010 person, This research purposes : For analysis hypertension patient lifestyle on public health center balingnipa sinjai regency. Ingredients and methods : this research use descriptive analytic research methods with approach cross sectionalyalti for do the measurement of independent variables (dietary habit) and dependet (hypertension patient). Then analyze the data who collected for collect the connection between variable research site implemented in public health center balangnipa north sinjai sub district sinjai regenc, this research implemented on april – may 2018.The research result : based on this research and after the data processing with chi-square for the dietary habit P value = 0,003< form value α= 0,05, so we can conclude there is relation between dietary habit and hypertension, after the data being process with chi-square we got P value = 0,007< form value α= 0,05, so we can conclude there is relation between alcohol habit and hypertension, after the data being process with chi-square we got P value = 0,011< form value α= 0,05, so we can conclude there is relation between smoking habit and hypertension, conclude from this research who do in public center balangnipa there is relation between alcohol consumption and hypertension incident on public health center, and there is relation between smoking habit with hypertension on balangnipa public health center Keyword : dietary habit, smoking habit, Alcohol Habit, Hypertension